Conversions in two-component dark sectors: a phase space level analysis - Shiuli Chatterjee; Andrzej Hryczuk (Journal of High Energy Physics)
Abstract Conversions between the states in the dark sector affect not only their number densities but also their momentum distributions. In this work we study a phenomenologically motivated two-component dark matter scenario, based on the Coy Dark Matter model, in order to quantify the effect of conversions on departure from kinetic equilibrium and consequently the relic abundance. We perform a detailed numerical analysis at the level of the phase space distributions of dark sector particles, implementing all the relevant processes, including conversions, elastic scatterings and annihilations. Focusing on the parameter regions that lead to the observed relic abundance and provide a good fit to the Galactic Centre excess, we find that departure from kinetic equilibrium can alter the predictions for the total abundance by more than 100%, while in most of the interesting parameter space being in the range from around −20% to 50%. The effect on each dark matter constituent separately can be much larger, even up to an order of magnitude, which can significantly affect the expected present-day gamma ray flux, and consequently phenomenology of the model.